The Effectiveness of Mindfulness-Based Stress Reduction on Catastrophizing and Pain Perception among Adolescents with Leukemia - Shirin Tarkeshdooz; Gholamreza Sanagouye-Moharer (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Catastrophizing and pain perception can cause more psychological problems among adolescents with leukemia. Therefore, medical interventions are effective in reducing psychological problems among adolescents with leukemia. The purpose of this study was to determine the effectiveness of mindfulness-based stress reduction on catastrophizing and pain perception among adolescents with Leukemia. Materials and Methods: The present study was of semi-experimental design with a pre-test-post-test and control group. The statistical population of this study included all adolescents with leukemia referred to Shariati Hospital in Tehran in 2016, among whom 60 (30 in the experimental and 30 in the control group) were selected by convenience sampling method and the intervention was conducted for the experimental group. The instrument was a McGill pain questionnaire and pain catastrophizing scale. Data analysis was performed using multivariate covariance analysis and one way covariance analysis using SPSS software version 22. Results: The mean (SD) age in the experimental group was 16.1 (5) and 15.1 (4.1) in the control group. The mean (SD) score of catastrophizing in experimental group was 39.8 (10.2) in pre-test, which decreased to 32.8 (8.8) in the post-test (P<0.01). The mean (SD) score of the control group was 37.7 (5.2) in the pre-test, which was 37.8 (6.5) in the post-test; however, it was not statistically significant. The mean (SD) score of the pain perception in the experimental group in the pre-test was 37.5 (8.1), which decreased to 33.4 (9.4) in post-test (P<0.01). However, the mean (SD) score of the control group in pre-test was 36.1 (4.9) which was 35.7 (6.6) in the post-test, which was not significant. Conclusion: The study showed that the mindfulness-based stress reduction can reduce catastrophizing and pain perception among adolescents with leukemia. DOI: http://doi.org/10.22037/ch.v6i3.22660.